Prekmurje Slovenes in the Hungarian Raba region and the boundaries of Prekmurje - Josipovič, Damir (Anali PAZU HD, 2022)
The Trianon Treaty from 1920 decisively influenced the shaping of Slovenian (then the Kingdom of Serbs, Croats, and Slovenes) – Hungarian border by posing the boundary onto the low, untypical watershed between the rivers of Raba and the Great Krka. Thus it curtailed the homogeneous Prekmurian speaking area of nine settlements against the Raba River. The treaty failed to convincingly justify the factors applied for delineation. North of this boundary remained some 7000 inhabitants who used the regional variation of the Prekmurian vernacular. Thenceforth the number of “Raba dialect” speakers systematically contracted to plummet to around 1000 as it was confirmed by the last population census from 2011. As a contrast, the number of self-declared Slovenes remained stable in the last decade and considerably higher compared to the number of the Slovene speakers itself. Beside the changed social relations with scarce possibilities of economic activity, the main factors reducing the numbers of Prekmurian and Slovene speakers were utmost emigration, low fertility, and depopulation.
Keywords: Porabje (Rába region); north-eastern (Pannonian) Slovenian dialects; population census; demography; Slovenian-Hungarian boundary; Trianon Treaty; Prekmurje (Trans-Mura region)